1991
DOI: 10.1073/pnas.88.7.2888
|View full text |Cite|
|
Sign up to set email alerts
|

Expression of the terminal protein region of hepatitis B virus inhibits cellular responses to interferons alpha and gamma and double-stranded RNA.

Abstract: Constructs expressing the core, surface, X, or polymerase proteins of hepatitis B virus were transfected into human cells. In transient assays, only the polymerase inhibited the responses to interferons a and y (IFN-a and -y). Stable expression of the polymerase was achieved in the cell line 2fTGH, which carries an IFN-inducible marker gene, by growth under conditions that select for inhibition of the response to IFN-a, but the clones grew poorly. When expressed alone, the terminal protein domain of the polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
55
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(63 citation statements)
references
References 38 publications
(35 reference statements)
7
55
1
Order By: Relevance
“…Several different mechanisms have been proposed to account for this effect (Sen & Ransohoff, 1993). HBV capsid protein (referred to as the HBc protein) has been shown to trans-suppress IFN-β gene expression (Whitten et al, 1991) ; whilst in another study, the expression of HBV polymerase terminal protein was shown to inhibit IFN-induced 6-16 gene expression (Foster et al, 1991). This latter result, however, is still debated (Foster et al, 1995).…”
Section: Introductionmentioning
confidence: 82%
“…Several different mechanisms have been proposed to account for this effect (Sen & Ransohoff, 1993). HBV capsid protein (referred to as the HBc protein) has been shown to trans-suppress IFN-β gene expression (Whitten et al, 1991) ; whilst in another study, the expression of HBV polymerase terminal protein was shown to inhibit IFN-induced 6-16 gene expression (Foster et al, 1991). This latter result, however, is still debated (Foster et al, 1995).…”
Section: Introductionmentioning
confidence: 82%
“…Our results support this idea and define a molecular basis for the synergy between IFNs and sodium butyrate in hepatoma growth inhibition. Furthermore, a recent study has reported that hepatitis B viral terminal protein shuts off IFN-induced gene expression by interfering with the formation of ISGF-3 and inhibited cellular responses to IFN-α and IFN-γ (Foster et al, 1991). The authors suggested that, in patients with chronic hepatitis B virus infection, an imbalance in HBV RNA and polymerase production may generate sufficient free polymerases or terminal proteins to give rise to IFN-resistant cells.…”
Section: Discussionmentioning
confidence: 99%
“…The RT protein is known to interact with a number of cellular proteins, including molecular chaperone proteins (13,15), the helicase DDX3 (52), and the translation factor eIF4E (22). The RT protein is also thought to be cytotoxic when overexpressed and has been reported to affect cellular functions such as interferon signaling and gene expression (2,8,14,53). Perhaps, the formation of nucleotide abducts of cellular proteins, i.e., RT-mediated protein priming from these cellular proteins, can contribute to the cellular effects of the RT protein and thus could play a role in cytotoxicity and viral pathogenesis, especially if substantial amounts of the RT protein are unpackaged (58).…”
Section: Discussionmentioning
confidence: 99%